(untitled) (ENTHYMEMA, 2023)
This paper examines the Internet’s negative characterization in contemporary literature. In the first part I discuss how often contemporary writers choose to ignore the Internet and its effects upon society in their works of fiction. In the second part I focus on two novels, The Circle and No One Is Talking About This, that put the Internet at the center of their stories in order to criticize it.